IL-1β Expression of Patients with Chronic Rhinosinusitis is negatively correlated with Lund-Mackay score (Nusantara Medical Science Journal, 2022)
Introduction: IL-1β is one of the proinflammatory cytokines which is commonly found in various diseases, including Chronic Rhinosinusitis (CRS). It has been widely targeted as a therapeutic approach for inflammatory diseases. However, study of IL-1β expression and its correlation with CT-Scan grading scores in CRS is still scarce. Objective: To investigate IL-1β expression based on immunohistochemical examination and analyse its correlation with Lund-Mackay score in CRS with and without polyps. Method: This analytic observational study was done on 50 patients: 25 subjects in the CRS with Nasal Polyps (CRSwNP) group and 25 subjects in the CRS without Nasal Polyps (CRSsNP) group. The uncinate process was taken for immunohistochemical examination of IL-1β. Lund-Mackay score was calculated based on CT-Scan of the paranasal sinus. Result: IL-1β expression in CRSsNP (mean=36.38) was significantly higher than that in the CRSwNP (mean=14.62) with p